Biologic Therapies for Giant Cell Arteritis - Harrington R (Dove Medical Press, 2021)
Robert Harrington,* Shamma Ahmad Al Nokhatha,* Richard Conway Department of Rheumatology, St. James’s Hospital, Dublin, Ireland*These authors contributed equally to this workCorrespondence: Richard ConwayDepartment of Rheumatology, St. James’s Hospital, James Street, Dublin 8, IrelandTel +353-14103721Fax +353-12836099Email drrichardconway@gmail.comAbstract: Glucocorticoids have been the mainstay of treatment in giant cell arteritis (GCA) for the past 70 years. Conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) have largely failed to show significant clinical efficacy or reduction of the glucocorticoid burden in GCA. Tocilizumab is the first biologic to make a substantial impact in GCA treatment. With the current understanding of GCA pathogenesis implicating multiple cytokines, notably interleukin (IL) 6, IL-12, IL-23, IL-1β, and the role of janus kinases (JAKs) and the signal transducer and activator of transcription (STAT) pathway in these cytokines, many biologics are currently being investigated in GCA. This review article looks at the existing evidence for biologic agents in GCA. In addition to tocilizumab, the potential role of ustekinumab, abatacept, JAK inhibitors and other promising biologics in GCA are discussed in detail. A treatment algorithm based on the best evidence to date is also presented.Keywords: giant cell arteritis, biologics, glucocorticoids